Development of Horticultural Supply Chain with Value Co-Creation to Improve Farmers' Competitiveness and Incomes - Muhammad Azka; Arfina Samangi; Muhammad Naufal; Tomy Perdana (Universitas Lampung, 2019)
Vegetables are one of the horticultural commodities that have high economic value and opportunity in the market. However, vegetables supply chain in Indonesia is often identified with the traditional supply chain of long marketing chains, difficult market access for farmers, low competitiveness, farmers’ low income, and injustice to supply chain actors, especially between farmers and wholesalers. In creating a structured supply chain, value co-creation intervention applied to synergize farmers and wholesalers in Ciwidey Sub-district to understand each other’s problems then seek solutions to solve them. This research has been conducted in Ciwidey Sub-district, West Java. This research aims to measure the competitiveness and farmers income of each wholesaler’s group before and after value co-creation intervention. The result shows that variables competitiveness and income of Sari Hejo Farmer Group and Hidayah Alam Farmer Group have significant positive changed, while one of three indicator variable of competitiveness has not significantly changed.